Human Brain Activity Time-Locked to Narrative Event Boundaries - Speer, Nicole K.; Zacks, Jeffrey M.; Reynolds, Jeremy R. (Psychological Science, 2007)
Readers structure narrative text into a series of events in order to understand and remember the text. In this study, subjects read brief narratives describing everyday activities while brain activity was recorded with functional magnetic resonance imaging. Subjects later read the stories again to divide them into large and small events. During the initial reading, points later identified as boundaries between events were associated with transient increases in activity in a number of brain regions whose activity was mediated by changes in the narrated situation, such as changes in characters' goals. These results indicate that the segmentation of narrated activities into events is a spontaneous part of reading, and that this process of segmentation is likely dependent on neural responses to changes in the narrated situation.